2021
DOI: 10.3390/rs13040674
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Characterization of a Coastal Mode-Water Eddy from Multiplatform Observations and a Data Reconstruction Method

Abstract: Coastal mesoscale eddies are important oceanic structures partially responsible for regulating ocean-shelf exchanges. However, their description and characterization are challenging; observations are often too scarce for studying their physical properties and environmental impacts at the required spatio-temporal resolution. Therefore, models and data extrapolation methods are key tools for this purpose. Observations from high-frequency radar, one satellite and two gliders, are used here to better characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The network has provided surface current hourly data (with 3 hours rolling average) since 2009, with some interruptions mostly due to maintenance stops or malfunctioning related to severe atmospheric conditions. The performance of this network for ocean currents measurements and its potential for the study of ocean processes and transport patterns have already been demonstrated by previous works (e.g., Rubio et al, 2011;Solabarrieta et al, 2014;Solabarrieta et al, 2015;Solabarrieta et al, 2016;Manso-Narvarte et al, 2018;Rubio et al, 2018;Rubio et al, 2019;Manso-Narvarte et al, 2020;Rubio et al, 2020;Manso-Narvarte et al, 2021;Ruiz et al, 2022). However, wave information has so far remained unexploited.…”
Section: Waves From the Euskoos Compact Hf Radarmentioning
confidence: 65%
See 1 more Smart Citation
“…The network has provided surface current hourly data (with 3 hours rolling average) since 2009, with some interruptions mostly due to maintenance stops or malfunctioning related to severe atmospheric conditions. The performance of this network for ocean currents measurements and its potential for the study of ocean processes and transport patterns have already been demonstrated by previous works (e.g., Rubio et al, 2011;Solabarrieta et al, 2014;Solabarrieta et al, 2015;Solabarrieta et al, 2016;Manso-Narvarte et al, 2018;Rubio et al, 2018;Rubio et al, 2019;Manso-Narvarte et al, 2020;Rubio et al, 2020;Manso-Narvarte et al, 2021;Ruiz et al, 2022). However, wave information has so far remained unexploited.…”
Section: Waves From the Euskoos Compact Hf Radarmentioning
confidence: 65%
“…BF is used by phased array radars while DF is mainly used by compact antennas. The EuskOOS SeaSonde ® compact HF radar (EuskOOS HF radar from now on) network has already been used to study surface coastal transport processes in the area in combination with multisource data (Rubio et al, 2011;Rubio et al, 2013;Solabarrieta et al, 2014;Solabarrieta et al, 2015;Solabarrieta et al, 2016;Manso-Narvarte et al, 2018;Rubio et al, 2018;Rubio et al, 2020;Manso-Narvarte et al, 2021). Besides measuring sea surface water velocity [Crombie (1955), Barrick et al, 1977, Paduan andRosenfeld (1996) and Paduan and Graber (1997)], the HF radar can also monitor waves (Lipa, 1978;Lipa and Barrick, 1982;Lipa and Nyden, 2005;Gurgel et al, 2006;Wyatt, 2011;Wyatt, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of such approaches can be found for instance in the case of the coastal HF radars (e.g. O'Donncha et al, 2014;Cianelli et al, 2015;Ren et al, 2015;Jordà et al, 2016, Manso-Narvarte et al, 2020, Manso-Narvarte et al, 2021. To obtain high-resolution subsurface current maps from the combination of HF radar data and other data sources in the water column is especially valuable for the development of services linked to biogeochemical and environmental issues, since plankton or pollutants can be located deeper in the water column and not only follow surface dynamics.…”
Section: Data Fusion and Aggregationmentioning
confidence: 99%
“…The South China Sea is a vital marginal sea in the Pacific region, holding significant geographical importance. Mesoscale eddies, a common oceanic phenomenon, play a crucial role in heat transfer and nutrient transport in the South China Sea [1]. Typically, mesoscale eddies can survive for several days or even years, with spatial scales ranging from tens to hundreds of kilometers.…”
Section: Introductionmentioning
confidence: 99%